Oil origin and migration direction in Wushi sag, Beibuwan Basin, South China Sea. (November 2022) - Yin, Jia; Wei, Lin; Fan, Caiwei; Xu, Changgui; Man, Yong; Hu, Desheng; Hu, Lin; Hou, Dujie
Abstract: The Wushi sag is one of the most important petroleum-bearing units located in the Beibuwan Basin, South China Sea. Insufficient understanding of oil origin and migration direction, and lack of characterizing oil differential accumulation distribution patterns in Wushi sag greatly restrict further hydrocarbon exploration. In this study, oil-source rock genetic relationships and migration directions were analyzed in detail by combining geochemical analysis of 45 source rock samples, 23 crude oil samples, 12 oil sandstone samples, and basin modeling results. The geochemical data show there is distinguishable heterogeneity in Liushagang Formation (Fm) source rock in Wushi sag, which is divided into two types. The first type (including the Member (Mbr) 2 3 and Mbr 3 of Liushagang Fm source rocks) was deposited in a weak reducing to suboxic and fresh to brackish water environment with a predominance of aquatic algal plankton input. The second type (including the Mbr 1 and Mbr 2 1 of Liushagang Fm source rocks) was deposited in a suboxic and fresh to brackish water environment with mixed inputs of aquatic algal plankton and terrestrial higher plants. Three groups of crude oils (A, B, and C) are identified using their physical properties and biomarker data. The group A oil is characterized by a higher abundance of oleanane, lower abundance of C30 4-methylsterane, higher values of Pr/Ph, and lighter δ 13 C values, and is mainly derived from the Mbr 2 1 of Liushagang Fm source rock. Group B and group C oils are characterized by a lower abundance of oleanane and higher abundance of C30 4-methylsterane, but present some differences in Pr/Ph and δ 13 C values. Both groups of oils are sourced from the Mbr 2 3 of Liushagang Fm source rock, and their differences in geochemical characteristics indicate the lateral heterogeneity of source rock. Oil migration directions are determined by combining maturity parameters, pyrrolic nitrogen compounds, and also basin modeling results. The preferential oil migration directions in Wushi sag are from the central to the northeast and south of the sag. The accumulation distribution of different groups of oils is mainly controlled by the vertical and lateral heterogeneity of Mbr 2 of Liushagang Fm source rock. Highlights: The Liushagang Formation source rocks exhibited significant differences in geochemical characteristics. Three groups of crude oil were classified based on the physical property, carbon isotope, and biomarker. The preferential oil migration directions were determined by a comprehensive analysis of geology and geochemistry. The accumulation distribution of different groups of oil was mainly controlled by the heterogeneity of source rock.